2017
DOI: 10.18632/oncotarget.20520
|View full text |Cite
|
Sign up to set email alerts
|

Differences in modifiable factors of oral squamous cell carcinoma in the upper and lower of oral fissure

Abstract: The aim of this study was to explore differences in the effects of modifiable factors on oral squamous cell carcinoma (OSCC) occurring in the lower oral fissure (LOF) and upper oral fissure (UOF). We conducted a case-control study with 697 OSCC patients (119 UOF and 578 LOF) and 1910 frequency-matched controls in Fujian province, China. Data on demographic characteristics and possible modifiable factors was collected using a structured questionnaire. Unconditional logistic regression was utilized to calculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Finally, according to our inclusive criteria mentioned in Materials and Methods, 14 articles were identified and included in the meta-analysis. [2942]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, according to our inclusive criteria mentioned in Materials and Methods, 14 articles were identified and included in the meta-analysis. [2942]…”
Section: Resultsmentioning
confidence: 99%
“…Through eligible literature searching process, 14 case–control studies [2942] including 5920 patients and 10553 controls were selected. Eight of them were performed in Asia, [2933,35,38,41] 2 studies were performed in America, [40,42] 3 studies were conducted in Europe, [34,37,39] and 1 study in Africa. [36] Three studies separately reported the mean age of participants <60 or >60 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations